Spatiotemporal Analysis of Shoreline Changes of the Kizilirmak Delta - Ozturk, Derya; Beyazit, Isik; Kilic, Fatmagul (COASTAL EDUCATION & RESEARCH FOUNDATION, 2015)
The detection of shoreline changes in coastal countries is critical for successful management and planning. Determining shoreline changes and investigating reasons behind uncontrolled changes ensure that the necessary precautions can be taken. This study focuses on determining temporal changes that have occurred on the shoreline of the Kizilirmak Delta, which is one of the most crucial wetlands protected by the Ramsar Convention in Turkey. Landsat-5 thematic mapper (TM) satellite images from 1987, 1998, 2002, 2007, and 2011 were used to determine temporal changes. The approach, which integrates band-ratioing and histogram-thresholding methods, was applied using the second, fourth, and fifth bands of the Landsat TM images. The shoreline change envelope (SCE), end point rate (EPR), and linear regression rate (LRR) methods were used to determine the shoreline changes. The SCE method detected a landward migration that occurred on the delta, where its maximum migration was 655.6 m between 1987 and 2011. During the same period, the maximum coastal change rate was estimated to be -27.4 m/y using the EPR method and -29.7 m/y using the LRR method. The maximum amount of erosion occurred near the river mouth. The results indicated that the dams built on the Kizilirmak River and close to the delta significantly affected these changes and that the spurs, which were built to prevent coastal erosion and provide partial protection, cannot fully prevent erosion.
Keywords: Coastal erosion; change detection; SCE; EPR; LRR; ISLAND; Environmental Sciences & Ecology; Physical Geography; Geology